Makna Kebebasan Dalam Filsafat Klasik Dan Relevansinya Bagi Kebebasan Manusia Modern - Victor Deak; Markus Suwandi; Solihin Bin Nidin (Jurnal Ilmu Sosial dan Humaniora, 2026)
This study explores the concept of freedom in classical philosophy by examining its relevance for constructing individual freedom in the modern context. Within contemporary culture where freedom is often reduced to absolute autonomy devoid of ethical grounding there emerges a crisis of meaning expressed through nihilism, hedonism, and radical individualism. Through a hermeneutical-philosophical approach, this study reinterprets the views of classical philosophers such as Socrates, Plato, Aristotle, and the Stoics, who understand freedom not as the absence of limits but as a moral and rational disposition that directs human beings toward self-mastery (enkrateia), practical wisdom (phronēsis), and a life in harmony with the cosmic moral order. The analysis shows that the classical philosophical tradition conceives freedom as a dual existential structure: external freedom, which demands liberation from external domination, and internal freedom, which is realized through moral discipline, the ordering of the soul, and the alignment of the will with logos. This perspective offers a corrective framework to modern conceptions of freedom that tend to be fragmented between the assertion of individual rights and a crisis of moral orientation. The theoretical gap addressed in this research lies in the absence of a comprehensive integration between classical virtue ethics and modern theories of freedom centered on subjective autonomy. The novelty of this study is its presentation of a conceptual synthesis that situates freedom as a dynamic relationship between rights, rationality, and moral responsibility. Thus, the study underscores the urgency of restoring a paradigm of freedom grounded in moral excellence not merely as a theoretical discourse but as a foundation for cultivating mature and responsible individual freedom.